Mechanical behaviour & fracture of uranium - Taplin, D (1964)
A study of the mechanical properties and fracture characteristics of four grades of reactor uranium has been carried out within the range -196°C and +800°C. Although the investigation is general and broadly-based without detailed examination of each aspect, particular emphasis has been placed upon the ductile/brittle transition which occurs at about room temperature. Having considered the scientific and technological interest in this field of uranium metallurgy, there follows a comprehensive review of the relevant published work. This includes a discussion of previous reports upon the structure, transformation mechanisms, deformation, fracture and mechanical properties of uranium together with a survey of current theories of fracture. The experimental work involved vacuum and lead bath heat treatment, tensile, notch bend, compression and hardness testing followed by bright-field, polarized light end replies metallography. An initial study of the microstructural effects of mechanical and thermal treatment showed how the required control of microstructural variables could be achieved. Additionally, this preliminary work suggested that the important criterion in grain-refinement upon beta-alpha quenching by alloying with iron and aluminium in the amount of dispersed network phase present which retards alpha grain growth. Contributory factors appear to be solution of these added elements in the beta phase and beta grain growth. Three modes of fracture were observed in the alpha phase: crystallographic (low temperature), intercrystalline (in the region of room temperature and ductile (above room temperature). It is considered that the best explanation for the process of crystallographic failure (twin parting) is that it is nucleated at the apices of growing thick twins by a reaction involving emissary dislocations. Propagation is suggested to occur along the composition planes of the twins because these are the sites of structural distortion and stress thereby providing planes of inherent weakness in the lattice. Tests after thermal cycling established that an intergranular path of fracture is favoured because the anisotropy of thermal expansion gives rise to residual grain boundary stresses to a varying degree after most heat treatments thereby lowering the surface energy for fracture in these areas. Ductile failure occurred by the formation of cavities at cuboid inclusions which grew and, in the centre of the externally necked region, coalesced to form a macroscopic fissure which propagated outwards to cause failure. Below about 300°c cavity formation tended to occur at an early stage by cuboid cleavage, whilst above 300°C cavities tended to be formed at a later stage by inclusion/matrix parting. The ductile/brittle transition cay be attributed to increasing dislocation friction stress with decreasing temperature such that stresses at twin apices and composition planes were not readily accommodated and parting failure thereby facilitated. It is possible that with decreasing temperature there is a change in the electronic configuration to cause stronger covalent bonding and the transition can be explained in these terms. All these changes in fracture behaviour are reflected in the tensile properties and consequently an explanation for the effect of temperature upon many of these properties follows. A number of variables were shown to lower the ductile/brittle transition temp- ature including:- a) decreasing volume fractions of the finely dispersed intermetallic network (i.e. increasing purity), b) decreasing grain size, c) increasing amounts of cold-work or pre-strain, d) decreasing strain-rate. These effects can be mainly explained by invoking current theories of fracture. Additionally the transition temperature was shown to be sensitive to heat treatment. Heat treatment can cause variations in the surface energy for fracture at grain boundaries giving rise to intercrystalline embrittlement and promoting brittle fracture, thus providing an explanation. The brittle (parting) fracture stress of polycrystalline alpha decreases progressively with decreasing temperature. This may be related to the anisotropic structure which results in a very low yield stress. No simple fracture stress/grain size (d) relationship was found but if account is taken of all the influencing factors in alpha uranium the results might be explained in terms of the usual d-½ relationship. Beta uranium was shown to be brittle both in the beta region (when fracture appears to take an intergranular path) and when retained to room temperature (and below) by quenching an iron and aluminium rich grade (when failure appears to be by crystallographic cleavage).